Lip Print Pattern among Children Visiting Dental Out patient department - Rai, Amita; Chaulagain, Rajib (Journal of Nepal Health Research Council, 2024)
Background: Lip print patterns are unique in every individual. The uniqueness of lip print pattern assists in the personal identification. The objectives of the present study were to study the different lip print patterns among the children visiting Kanti Children’s Hospital, and to compare the distribution of lip print patterns based on gender and race. Methods: A cross-sectional study was conducted among 300 children visiting the Dental Outpatient Department of Kanti Children’s Hospital, Kathmandu, Nepal. Convenience sampling method was used to choose the study subjects. Digital photography method was used to record the image of lips. Results: The study showed ‘Long vertical’ (Type I) as the most frequent (41%) type of lip print pattern, whereas ‘Unspecified’ (Type V) was the least frequent (2.7%) type. Prevalence of ‘Type I’ pattern was significantly higher in males as compared to females (p=0.007) whereas prevalence of ‘Type IV’ pattern was significantly higher in females as compared to males (p=0.006). ‘Type I’ pattern was the commonest lip print pattern among both Caucasians and Mongolian, whereas ‘Type V’ (2%) and ‘Type IV’ (3.7%) were the least common lip print patterns in Caucasians and Mongolian children respectively. Conclusions: ‘Long vertical’ (Type I) was the most common lip print pattern among the children visiting the Dental Outpatient Department of Kanti Children’s Hospital, Kathmandu, Nepal. Nevertheless, in higher or lesser numbers, all kinds of lip print patterns as described by Suzuki and Tsuchihashi were seen in the study population. Keywords: Children; gender; lip print patterns; race.